Quality and shelf-life extension of refrigerated (4°C) Spotted snakehead (Channa punctata) using γ-radiation and food-grade preservative (Jahangirnagar University Journal of Biological Sciences, 2021)
Investigations were carried out to evaluate the effect of gamma radiation (1.0 and 1.5 kGy) and food-grade preservative (2% potassium sorbate) on the shelf-life of refrigerated (4°C) Spotted snakehead, Channa punctata (Bloch, 1793). Quality assessments were evaluated by sensory (OS), chemical (TV), microbial (TBC and TCC) analyses. Based on control panel, OS was shown to be gradually decreased with the storage time. Irradiated and potassium sorbate treated samples were found acceptable (edible) up to 28 and 21 days, respectively of storage period. TV were lower in irradiated samples with dose of 1.5 kGy compared to other samples. Though microbial load of each of the irradiated samples were within the acceptable limits up to 28 days but 1.5 kGy dose was found more effective. Gamma radiation in combination with good refrigeration could be most effective treatment for the shelf-life extension and microbiological quality improvement for snakehead preservation. Moreover, this preservation technique may be applicable for other fish species to enhance food safety for public health issues.Jahangirnagar University J. Biol. Sci. 9(1 & 2): 1-12, 2020 (June & December)